The Formation of the Professional and Pedagogical Culture of a Teacher of a Pedagogical Higher Education Institution: Trends and Principles - Repko, Inna; Stepanets, Ivan (Pedagogical Discourse, 2022)
The article examines and characterizes the highlighted key trends and principles of the formation of the professional and pedagogical culture of a teacher of a higher pedagogical education institution in the context of its innovative development. Based on the generalization of scientific theory and own pedagogical experience, the concept of professional and pedagogical culture of a teacher of a modern pedagogical higher education institution is specified, the main contradictions that stimulate the process of its formation and development are formulated. Pedagogical theory and practice are enriched with theoretical and theoretical-methodological provisions regarding modern characteristics and methodological approaches to the formation and development of the professional-pedagogical culture of a teacher of a pedagogical higher education institution. Common structural components are named and the unity of the ratio of educational and scientific activity of the teacher is characterized as a condition for the effectiveness of the development of his professional and pedagogical culture. The results of scientific research illustrating the implementation of certain principles and indicating the factors of the effectiveness of the innovative activity of teachers are given, and the conditions of its influence on the level of formation of professional and pedagogical culture are given. By summarizing practical experience and research results, the psychological and pedagogical conditions that affect the development of professionally significant personal values of teachers of higher education institutions are singled out. With the help of a structural-logistic scheme, the integration and relationship of socio-cultural and professional values of a teacher of a higher pedagogical institution of education as elements of his professional and pedagogical culture are presented. Prospects for further research on the specified problem are outlined.